2009
DOI: 10.1007/s10552-009-9359-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients with prostate cancer are less likely to develop oesophageal adenocarcinoma: could androgens have a role in the aetiology of oesophageal adenocarcinoma?

Abstract: Oesophageal adenocarcinoma (OAC) is more common in men. Androgens may therefore contribute to the pathogenesis of OAC. Prostate cancer (PC), an androgen sensitive tumor with a long natural history, may allow insights into this putative association. West Midlands Cancer Intelligence Unit data from 1977 to 2004 were examined to identify patients with a first malignant primary of PC. Patients were followed until diagnosis of a second primary cancer, death or end of the time period. Age- and period-adjusted standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
2
22
3
Order By: Relevance
“…However, a putative molecular basis for androgens contributing to the oncogenesis of EAC has been reported [9][10][11], and more recently, we reported epidemiological evidence of a reduced incidence of EAC following PC [14], a condition frequently treated with anti-androgen therapy [15]. In our previous study, we could not identify a latency effect that would support the hypothesis that androgens play a role in the etiology of EAC, but postulated that the lack of an effect was likely to be due to a relative lack of power to demonstrate it [14].…”
Section: Black Malesmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a putative molecular basis for androgens contributing to the oncogenesis of EAC has been reported [9][10][11], and more recently, we reported epidemiological evidence of a reduced incidence of EAC following PC [14], a condition frequently treated with anti-androgen therapy [15]. In our previous study, we could not identify a latency effect that would support the hypothesis that androgens play a role in the etiology of EAC, but postulated that the lack of an effect was likely to be due to a relative lack of power to demonstrate it [14].…”
Section: Black Malesmentioning
confidence: 94%
“…We have previously investigated the hypothesis that androgens may contribute to the etiology of EAC by identifying subjects with a first primary of prostate cancer, an androgen-sensitive tumor [12] with a long natural history (5 year survival of over 70 % for those presenting without metastases [13]), in the West Midlands Cancer Intelligence Unit registry (UK) and examining the risk of developing a second cancer of the esophagus, compared with the general population [14]. The study identified a reduced risk of developing EAC following prostate cancer (PC), but not esophageal squamous cell carcinoma (ESCC).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid rise in the incidence of oesophageal adenocarcinoma in Western societies during recent decades (Brown et al , 2008) has been especially pronounced in men (Vizcaino et al , 2002). Epidemiological studies evaluating the hypothesis that sex hormones have a role, including hormonal replacement therapy (Lindblad et al , 2006) and reproductive factors (Lagergren and Jansson, 2005), have not provided support for oestrogen as an aetiological factor, whereas reports on anti-androgen therapy have shown mixed results (Lagergren and Nyren, 1998; Cooper et al , 2009). Furthermore, there seem to be no clear sex differences in the strength of the associations between known risk factors and risk of oesophageal adenocarcinoma (Hampel et al , 2005; Lindblad et al , 2005; Kubo and Corley, 2006).…”
mentioning
confidence: 99%
“…Individuals diagnosed with prostate cancer, who often receive some form of androgen deprivation therapy which severely reduces testosterone and DHT levels, have shown reduced risks of esophageal adenocarcinoma with standardized incidence ratios (SIR) of 0.83 (p<0.05) in a US population 29 and 0.70 (p<0.05) in a UK population 30 .…”
Section: Discussionmentioning
confidence: 99%